Quality of life assessment in patients with chronic rhinosinusitis by using rhinosinusitis disability index - Buddaraju, Varaprasada V.; Chilukuri, Ramya S.; Gonuru, Vinod K.; Dandala, Sridhar R. (International Journal of Research in Medical Sciences, 2024)
Background: Chronic rhinosinusitis is a common disease affecting the nose and paranasal sinuses. One of the commonly used indices to assess the impact of chronic rhinosinusitis on quality of life is the rhinosinusitis disability index (RSDI). Objective was to study the surgical techniques and surgical findings of all patients with chronic rhinosinusitis undergoing endoscopic sinus surgery and to compare pre-surgical with post-surgical RSDI score. Methods: The patients were given RSDI questionnaire forms which contain questions regarding physical, functional and emotional factors which will be answered before and 3 months after endoscopic sinus surgery. The surgical technique and surgical findings of all patients undergoing the surgery are studied. The pre-surgical and post-surgical RSDI scores are compared and analysed by the Wilcoxon sign rank test. Results: Uncinectomy and middle meatal antrostomy were performed in all the patients undergoing functional endoscopic sinus surgery. Wilcoxon sign rank test is done to assess the difference in the pre and post-operative RSDI score and found to be statistically significant with p value <0.001 which indicates improvement in the RSDI score following functional endoscopic sinus surgery. Conclusions: RSDI is a valuable tool in assessing the health-related quality of life in patients with chronic rhinosinusitis.